Two phase motor fed from controlled supply - Shousha, H.; Ali, Sara; B. Kotb, A. (IAES International Journal of Robotics and Automation (IJRA), 2020)
Compared to single phase operation, a good utilization of machine material is achieved by supplying the two-phase stator windings from a controlled supply. It is necessary to start from the known equivalent circuits of both forward and backward components to obtain the relations between the sequence and the phase voltage values. In this method of control, the torque expression is driven in a simple form and the torque speed characteristic are computed and plotted for different values of the time-phase angle. The operation of 2-phase motor from single phase supply carried out by connecting one stator phase directly to the voltages source, with exciting the second stator phase through the phase shifting element. In this method, the starting and the maximum torque values can be controlled by changing the stator field from a pulsating of (0°) to a pure rotating field at (90°).